HUBUNGAN ANTARA PENGGUNAAN DOT DALAM PEMBERIAN SUSU FORMULA DENGAN KEJADIAN CARIES GIGI BALITA USIA 4-5 TAHUN DI TK TARBIYATUSH SHIBYAN DESA GAYAMAN KECAMATAN MOJOANYAR MOJOKERTO - Nurhidayah, Evi; Diana, Sulis (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2013)
Caries Tooth of merupaka disease that happened at hard network of tooth (Enamel and of dentin). 85% child of balita in Indonesia experience of tooth caries. The root cause its it him tooth caries at child is triggered by gift of milky sweet condensation of formula use dot all day long till fall asleep. Target of this research to know relation between usage of dot in giving of milk of formula with occurence of tooth caries at age balita 4-5 year in TK Tarbiyatus Countryside Style shibyan District Of Mojoanyar Sub-Province of Mojokerto. Type Research use analytic observation desain of correlation with approach of secsional cross . Independent variable of him is usage of dot and variable its him is occurence of tooth caries. Its population all age balita 4-5 year that is 44 child and its its[his] 44 child. Using technique of nonprobabiliti sampling with intake of sampel totally sampling. This research is conducted on 7 Mei-7 June 2012, instrument research of observation and interview. Data analysis use test of chi square Bigger of usage of dot in giving of milk of formula responder is given by counted 23 people (63.9%). Most natural responder of tooth caries counted 26 people ( 72.2 is%). Bigger of usage of dot in giving of milk of formula with occurence of tooth caries counted 21 people (58.3%).Pursuant to result of test of chi square with result of result of X2[count/calculate] : 11,560b > X2Tabel : 3,841 : its 0,001 meaning of H1 accepted by Ho refused by there is relation among usage of dot with occurence of tooth caries at age balita 4-5 year in TK Shibyan Countryside Style tarbiyatush District Of Mojoanyar Sub-Province of Mojokerto.Conclusion of which can pulled by is usage of dot can cause tooth caries if given all day long. For mother so that accustoming child drink milk use glass and also learn and health energy can cooperate to be more often conduct inspection of tooth Keyword : Caries Tooth, Usage of Dot, Childern